Study on synthesis and characterization of electrocatalyst containing platinum, palladium, nickel for hydrogen evolution reaction in alkaline medium - Nguyen Thi Cam Ha; Huynh Thi Lan Phuong; Nguyen Huu Tho; Nguyen Van Thuc (My University, 2020)
Study on synthesis and characterization of electrocatalyst containing platinum, palladium, nickel for hydrogen evolution reaction in alkaline medium
Keywords: Electrocatalyst